Respuesta :
Answer:
[tex]\displaystyle P_2(x) = 3 + \frac{1}{3}(x - 1) + \frac{4}{27}(x - 1)^2[/tex]
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Algebra I
Functions
- Function Notation
Calculus
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Addition/Subtraction]: [tex]\displaystyle \frac{d}{dx}[f(x) + g(x)] = \frac{d}{dx}[f(x)] + \frac{d}{dx}[g(x)][/tex]
Basic Power Rule:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Derivative Rule [Chain Rule]: [tex]\displaystyle \frac{d}{dx}[f(g(x))] =f'(g(x)) \cdot g'(x)[/tex]
Taylor Polynomials
- Approximating Transcendental and Elementary Functions
- [tex]\displaystyle P_n(x) = \frac{f(c)}{0!} + \frac{f'(c)}{1!}(x - c) + \frac{f''(c)}{2!}(x - c)^2 + \frac{f'''(c)}{3!}(x - c)^3 + ... + \frac{f^n(c)}{n!}(x - c)^n[/tex]
Step-by-step explanation:
*Note: I will not be showing the work for derivatives as it is relatively straightforward. If you request for me to show that portion, please leave a comment so I can add it. I will also not show work for elementary calculations.
Step 1: Define
Identify
f(x) = √(x² + 8)
Center: x = 1
n = 2
Step 2: Differentiate
- [Function] 1st Derivative: [tex]\displaystyle f'(x) = \frac{x}{\sqrt{x^2 + 8}}[/tex]
- [Function] 2nd Derivative: [tex]\displaystyle f''(x) = \frac{8}{(x^2 + 8)^\bigg{\frac{3}{2}}}[/tex]
Step 3: Evaluate
- Substitute in center x [Function]: [tex]\displaystyle f(1) = \sqrt{1^2 + 8}[/tex]
- Simplify: [tex]\displaystyle f(1) = 3[/tex]
- Substitute in center x [1st Derivative]: [tex]\displaystyle f'(1) = \frac{1}{\sqrt{1^2 + 8}}[/tex]
- Simplify: [tex]\displaystyle f'(1) = \frac{1}{3}[/tex]
- Substitute in center x [2nd Derivative]: [tex]\displaystyle f''(1) = \frac{8}{(1^2 + 8)^\bigg{\frac{3}{2}}}[/tex]
- Simplify: [tex]\displaystyle f''(1) = \frac{8}{27}[/tex]
Step 4: Write Taylor Polynomial
- Substitute in derivative function values [Taylor Polynomial]: [tex]\displaystyle P_2(x) = \frac{3}{0!} + \frac{\frac{1}{3}}{1!}(x - c) + \frac{\frac{8}{27}}{2!}(x - c)^2[/tex]
- Simplify: [tex]\displaystyle P_2(x) = 3 + \frac{1}{3}(x - c) + \frac{4}{27}(x - c)^2[/tex]
- Substitute in center c: [tex]\displaystyle P_2(x) = 3 + \frac{1}{3}(x - 1) + \frac{4}{27}(x - 1)^2[/tex]
Topic: AP Calculus BC (Calculus I + II)
Unit: Taylor Polynomials and Approximations
Book: College Calculus 10e